2010
DOI: 10.1212/wnl.0b013e3181f25f06
|View full text |Cite
|
Sign up to set email alerts
|

Progression of brain atrophy and cognitive decline in diabetes mellitus

Abstract: Our data show that elderly patients with DM without dementia have accelerated progression of brain atrophy with significant consequences in cognition compared to subjects without DM. Our findings add further evidence to the hypothesis that diabetes exerts deleterious effects on neuronal integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
143
5
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(158 citation statements)
references
References 37 publications
(38 reference statements)
8
143
5
2
Order By: Relevance
“…The reduction in mean total brain volume is 0.2-0.6 SD units, comparable with 3-5 years of normal aging (16)(17)(18). Longitudinal case-control and population-based studies have demonstrated brain volume loss in patients with diabetes that is similar to or up to three times the atrophy rate of normal aging (16)(17)(18)(19). The loss of brain tissue is most clearly reflected by accelerated expansion of the ventricles (16,17,19).…”
Section: Type 2 Diabetesmentioning
confidence: 76%
See 3 more Smart Citations
“…The reduction in mean total brain volume is 0.2-0.6 SD units, comparable with 3-5 years of normal aging (16)(17)(18). Longitudinal case-control and population-based studies have demonstrated brain volume loss in patients with diabetes that is similar to or up to three times the atrophy rate of normal aging (16)(17)(18)(19). The loss of brain tissue is most clearly reflected by accelerated expansion of the ventricles (16,17,19).…”
Section: Type 2 Diabetesmentioning
confidence: 76%
“…Most crosssectional studies report an association between brain volume and executive functioning or processing speed (21). One longitudinal study found an association between baseline brain atrophy and decline in immediate memory but not in delayed memory (18). Two studies directly examined whether brain volume mediated the relationship between type 2 diabetes and cognitive dysfunction and reported contrasting results: gray matter volume significantly mediated the relationship with executive functioning and memory in one study (22), but in another study, between-group differences in cognition were largely independent of MRI markers of brain atrophy (19).…”
Section: Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies of structural magnetic resonance imaging (MRI) show that in T2D cognitive impairment is associated with greater levels of vascular lesions as well as with brain atrophy [6][7][8][9][10] . Prospective MRI studies also show that in T2D brain atrophy occurs at faster rates than in normal ageing 11,12 , suggesting that T2D accelerates neurodegeneration. Animal studies provide additional evidence to show that inducing T2D/insulin resistance (IR) can promote the pathological changes characteristic of Alzheimer's disease (AD), specifically accumulation of amyloid-beta (Aβ) and tau (see review ref.…”
Section: Growing Evidence Supports the Hypothesis That Type 2 Diabetementioning
confidence: 97%